Analisis Pengaruh Internet Marketing Terhadap Pembentukan Brand Awarness Pada Perusahaan Grosir Pakaian OMR Group Solo - Wibowo, Arif puguh Priyambodo (2016)
This study aims to determine how much influence the personal relevance, interactivity, message, brand familiarity to the formation of brand awareness in the company's wholesale clothing OMR Group Solo and determine the dominant variable affecting the formation of brand awareness in the company's wholesale clothing OMR Group Solo. Based on the results of this research can be used as a material consideration in the evaluation of online consumers shop with product perception, the perception of the source, perceptions of advertising, attitude toward the brand and attitudes toward advertising. Testing the hypothesis in this study using regression analysis moderating with t-test, F and coefficient of determination (R2). The population of this research is all consumer OMR Group Solo.Teknik sampling in this study using simple random sampling technique, so that the OMR Group acquired 100 consumers Solo as the study sample. Based on the survey results revealed that personal relevance, interactivity, message and brand familiarity positive and significant impact on the formation of the company's brand awareness wholesale clothing OMR Group Solo. This indicates that social networking sites are used because they have superb connectivity between the customer and the community that has been formed therein. Personal Relevance dominin have the most influence on the formation of the company's brand awareness wholesale clothing OMR Group Solo, this shows that personal relevance has the ability of a brand to appear in consumers' minds when they're thinking about a specific product category and how easy it is these names appear. Keywords: personal relevance, interactivity, message, brand familiarity, brand awareness